Reconstructing collaborative (self-)translations from the archive: The case of Samuel Beckett - Verhulst, Pim; Beloborodova, Olga; Van Hulle, Dirk (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2021)
When literary authors translate their own work, they sometimes collaborate with other writer-translators. While such “collaboration” is often acknowledged on the title pages of the resulting publications, the nature of each joint venture is typically very different in practice. Surviving archival traces often allow for a more detailed reconstruction of the varying working methods that were adopted for every co-translation, but it would be naïve to assume that even the most completely preserved record will make it possible to conclusively identify the function of every participant in the creative process. In this article, we will combine genetic criticism and genetic translation studies on the one hand, with microhistorical and social approaches to translation on the other, as complementary methodologies to further investigate the understudied notion of collaborative (self-)translation. By using as our test case the extant draft versions and other related materials that document the collaborative relationships between Irish bilingual author Samuel Beckett and his co-translators in French, English and German, the purpose is to show that a process-oriented and interdisciplinary approach to translation can help overcome some of the challenges and limitations presented by digital editions and archives such as the Beckett Digital Manuscript Project (BDMP).